Trend of Employee Engagement Research in Human Resource Management: A Content Analysis of Work-Life Balance and Leadership Studies - Trisanti, Ayu; Silalahi, Donalson (International Journal of Economics and Management, 2026)
Employee engagement has become a central concept in Human Resource Management (HRM) research due to its role in enhancing employee performance and organizational sustainability. This study employed a content analysis approach to review research trends related to employee engagement, particularly those examining work-life balance and leadership perspectives. A total of 50 peer-reviewed studies published between 2014 and 2025 were analyzed based on research design, antecedent variables, organizational context, theoretical frameworks, and methodological approaches. The findings indicate a significant increase in employee engagement research in recent years, with quantitative cross-sectional designs dominating the literature. Work-life balance and servant leadership emerged as the most frequently examined antecedents of employee engagement, while employee performance remained the primary outcome variable. Job Demands–Resources (JD–R) Theory was identified as the dominant theoretical framework. Based on the findings, this study proposes methodological and contextual recommendations for future employee engagement research.